Trust-based negotiation in multiagent systems: a systematic review - Barbosa, Ricardo (2023)
In this work, we conducted a systematic review on trust-based negotiation in Multiagent Systems (MAS), through a bibliometric analysis over the past 25 years of research publications, on three of the most popular scientific databases (Google Scholar, Scopus, and Web of Science). Our analysis reveals that this research topic is regaining interest, after some oscillating years, and the impact of its contributions is equivalent to other equally important research variants like ontology and argumentation (in a negotiation scenario). Discarding the human-to-agent trust challenges, we only focus on agent-to-agent trust concepts, and we performed an analysis of the different types of trust dimensions, using the findings and concerns of past review works, as we identify and select the dimensions that, in our opinion, have the most potential to lead the research advances on the topic of trust in MAS. Furthermore, we discuss the current challenges and open issues associated with those trust dimensions, and how current advancements in the literature could provide insights for the solution of those challenges, or even the finding of new research paths.